An Efficient Improved Weighted Round Robin Load Balancing Algorithm in Cloud Computing - N, Manikandan; A, Pravin (International Journal of Engineering and Technology, 2018)
Cloud Computing is an era when various trends showed up. It is the type of development, based solely on the Internet. The computer technology has brought in several changes along the years. SaaS is an architecture that comes under computing technology, involving the use of powerful processors, that helps in transforming data centers, scaling services involving computing technology across all fields. Various trends are opening in the field of Cloud Computing, developed mainly on Internet basis and use of computing technology. The computing architecture of SaaS along with powerful processors, are transforming data centers into a huge scale of pools of computing services.Â  Balancing load efficiently is one of the key areas involved in cloud computing. Services that are of very high quality can be subscribed for lower cost, along with completely reliable network connections with their bandwidth being increased , providing a flexible service residing in remote data centers. Load Balancing is the concept involved in the storage of computing resources. It is the partition of work which requires processing between two or more number of computers and/or CPUs, storage devices which ultimately leads to providing higher efficiency with much faster service. The improved WRR algorithm which is improved has been proposed in order to distribute the workload efficiently, thereby enhancing various other features that are associated with it.Â Â